Políticas públicas de avaliação do Estado de São Paulo e as repercussões na prática pedagógica: SARESP em foco - Peixoto, Jociene Santos (2012)
Since 1996 with the law of Diretrizes e Bases da Educação Nacional (Guidelines and Bases of National Education) that settles the mandatory of the Brazilian government to evaluate its educational system, Education Department of the State of São Paulo made the Performance Evaluation System (SARESP). That kind of test is applied every year to final levels in the middle and high school, specially in the last degrees. The grade of that test added with school assiduity serves as base to calculate the Educational Development Index in the State of São Paulo (IDESP). The early 2008 has marked an important changes in Brazilian educational system. Since then, São Paulo s Government has paid a kind of plus to teachers who work at public schools. However just teachers who achieve the goals settled by the Government of the State of São Paulo can receive the plus in their own salaries. This way as teacher of public school in the State of São Paulo I have started to question myself if that kind of measure has some influence in work's teachers in the classroom. According to some experts in educational issues, SARESP could have an attribute more pedagogical and less formal and statistical. These experts agree that all educational evaluation system must really to evaluate the teaching instead of pursuing just its political legitimation. About our investigation, under qualitative methodology of search some teachers answered questionnaries and they did interviews. The open questionnaire and the interviews were conducted with teachers who work in the fourth year (Middle School). The result of the studies with teachers have shown that SARESP has been planned as an end in itself. SARESP method has been responsible for inserting inside of the teaching system a mechanism in which teachers teach just issues from own SARESP